Knowledge mapping concerning applications of nanocomposite hydrogels for drug delivery: A bibliometric and visualized study (2003–2022) - Wang, Hao; Fu, Hongxun; Fu, Yefan; Jiang, Lin; Wang, Liye; Tong, Haibin; Xie, Zuoxu; Huang, Peng; Sun, Meiyan (Frontiers in Bioengineering and Biotechnology, 2023)
Nanocomposite Hydrogels (NHs) are 3D molecular networks formed by physically or covalently crosslinking polymer with nanoparticles or nanostructures, which are particularly suitable for serving as carriers for drug delivery systems. Many articles pertaining to the applications of NHs for drug delivery have been published, however, the use of bibliometric and visualized analysis in this area remains unstudied. We identified and retrieved the publications concerning the applications of NHs for drug delivery between 2003 and 2022 from Web of Science Core Collection (WoSCC). Bibliometric and visualized analysis employing CiteSpace software and R-language package Bibliometrix were performed in this study.This analysis offered an investigative study and comprehensive understanding of publications regarding the applications of NHs for drug delivery from 2003 to 2022. The outcome of this study would provide insights for researchers in the field of NHs applications for drug delivery.